The Impact of Copycat Brand on Copycat Avoidance: the Moderating Role of Consumer Ethics - Mohsen Akbari; Mostafa Ebrahimpour Azbari; Abbas Darjani (کاوش‌های مدیریت بازرگانی, 2019)
Because of the importance of brand in consumers' decision-making, market leaders have invested heavily in their brands. In the meantime, follower companies try to imitate the brands of market leaders. Consumers, with their ethical differences, also show different reactions to this imitation. The purpose of this study is to investigate the role of the type of copycat (imitation) on the consumers' copycat avoidance with the moderating role of consumer ethics. In order to investigate this effect, the consumers of hypermarkets were surveyed through distributing a questionnaire. The collected data were analyzed by using the structural equation model (SEM) and the PLS software.The results show that, when a company imitates the apparent features or themes of a brand (theme copycat), it leads to copycat avoidance by consumers. Also, customer's ethics moderates the effect of appearance imitation on the copycat avoidance, but it does not have a moderating effect on the relationship between theme imitation and copycat avoidance by consumers.